ANALISIS IMPLEMENTASI KEBIJAKAN KULIAH DARING (ONLINE) SELAMA PANDEMI COVID-19 DI POLITEKNIK NEGERI BANDUNG - Mia Rosmiati (Universitas Sultan Ageng Tirtayasa, 2021)
The Covid-19 pandemic that has been occurred in the world including Indonesia, has plunged almost all important sectors in every country and the education sector is a sector that has had a significant impact, requiring policy changes in its implementation. The purpose of this research is to find out how the policies implemented regarding the educational patterns implemented at the Bandung State Polytechnic during the Covid-19 pandemic and how the results achieved by implementing educational policies in the era of the Covid-19 pandemic. The methods used in this study are descriptive qualitative wherein it describes the results of the acquisition and analysis of data in depth regarding the application of online lecture policies (Online). The data collected is in the form of primary data obtained through direct interviews with informants or resource persons and secondary data obtained from various literary sources related to educational information during the Covid-19 pandemic. The results obtained from this study are that with the policy of new learning methods during the Covid-19 pandemic, it can still produce good output in the sense that students can attend lectures well which are supported by various learning facilities prepared by the institution itself through a teaching and learning activity assistance program during the Covid-19 pandemic. The Covid-19 virus is not gone yet and still it threatens the safety of mankind so that education in Indonesia seems to be implemented through online methods, therefore management is expected to further improve the quality of learning to be even better so that Polban can still produce superior future generations and ready to compete with other parties in the world of work.